Genotype-dependent cell tropism of EV-A71 at the human blood cerebrospinal fluid and blood brain barrier - Hügel, Alina; Weiß, Christel; Ishikawa, Hiroshi; Stump-Guthier, Carolin; Schwerk, Christian; Schroten, Horst; Adams, Ortwin; Boettcher, Sindy; Diedrich, Sabine; Tenenbaum, Tobias; Rudolph, Henriette (Microbial pathogenesis, 2026)
Background - Enterovirus A 71 (EV-A71) has caused major epidemics worldwide. While it is most commonly associated with Hand-Foot-Mouth Disease (HFMD) or nonspecific presentations as upper or lower respiratory tract infection, it can also lead to severe neurologic manifestations especially in young children. Detailed understanding of the pathogenesis of EV-A71 CNS invasion as well as of the neurotropic subgenotypes is currently lacking. - Methods - EV-A71 infection at the level of the brain barriers was assessed with human in vitro models of the Blood-Cerebrospinal Fluid Barrier (BCSFB) using Human choroid plexus papilloma (HIBCPP) cells and the Blood-Brain Barrier (BBB) using Human brain microvascular endothelial cells (HBMEC). Six clinically relevant genotypes, namely BrCr, B5, C1, C1-like, C2 and C4 were compared. Besides BrCr, the reference strain for EV-A71 and C2, which is known for its worldwide presence, C1 and C1-like were chosen as they are mainly circulating in Europe whereas C4 and B5 are mainly known from the Asian-Pacific region. Infection was analyzed qualitatively via cytopathic effect (CPE) with light microscopy and immunofluorescence staining. Quantification of viral genome copies was performed via qPCR. In parallel, barrier integrity of the BCSFB was monitored via measurement of transepithelial resistance. LIVE/DEAD assays were applied for viability controls. - Results - HIBCPP cells and HBMEC differed in their susceptibility to infection with different genotypes of EV-A71 namely BrCr, B5, C1, C1-like, C2 and C4. None of the strains caused a lytic infection in either model, in contrast to infection in RD cells. In HIBCPP cells as a model for the BCSFB, B5 led to the highest infection rates. Significant differences in the polar release of viral progeny to the CSF side were detected for B5 (56.42 ± 7.13 %) compared to BrCR (30.39 ± 8.11 %), C1 (8.73 ± 8.89 %), C1-like (23.90 ± 17.28 %), C2 (16.89 ± 8.95 %) and C4 (21.46 ± 3.16 %). In HBMEC as a model for the BBB, BrCr showed significantly higher apical release compared to the other genotypes. The minimum p-value (0.0019) was recorded for pBrCr vs.B5 at 24 h and 48 h, while the maximum p-value (0.0379) was observed for pBrCr vs.B5 at 72 h. - Conclusion - Our findings reveal that different genotypes of EV-A71 exhibit distinct tropisms at the level of the brain barriers, which may correlate with variations in the clinical course of infection. Clinical and molecular surveillance of EV infections beyond those currently established in the Asia-Pacific region is warranted.
Online verfügbar: 22. Oktober 2025, Artikelversion: 24. Oktober 2025
Gesehen am 01.12.2025